Effects of specific resistance training in swimming on drag, propulsive power and propelling efficiency - Ogita, F.; Yamanaka, D.; Yotani, K.; Tamaki, H. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The present study aimed to examine the effects of specific resistance training using a fixed push-off point (POP) system on the drag-swimming speed relationship, maximal propulsive power (MPP) and propelling efficiency (ep). Six-teen well-trained male college swimmers (age 20 ± 1 years) were randomized into two groups, a control group (CON, n=8) and a resistance swimming group (RT, n=8). Training and all measurements in this study were performed in arm stroke of front crawl swimming. The training consisted of 10 arm stroke sprints of 25 m with (RT) or without (CON) the POP system, and it was conducted 3 days/week for 5 weeks. The active drag force and MPP were directly measured using measuring active drag (MAD) system. Propelling efficiency was determined according to the method described by Toussaint (1988). After the 5 weeks of training, no significant changes were observed in all variables in CON. In RT, the drag-swimming speed relationship and ep did not change significantly, either. However, MPP increased significantly from 182 W to 207 W (P<0.01) in this group. Furthermore, both the maximal propulsive force (P<0.01) and maximal swimming speed (P<0.01) at which MPP was obtained on MAD system increased significantly in RT. These results revealed that specific resistance swimming using a POP system can improve maximal propulsive power, which suggests that it is a beneficial training method to improve sprint swimming performance. In contrast, this kind of training does not appear to reduce active drag or improving swimming efficiency.